A STUDY OF THE PERFORMANCE OF THE MODIFIED TRANSFORMED VEGETATION INDEX MTVI - Skianis, G. Aim.; Gournelos, Th.; Vaiopoulos, D.; Nikolakopoulos, K. (Bulletin of the Geological Society of Greece, 2010)
In the context of a recent research on the performance of vegetation indices we have shown, with the aid of probability theory, that the shape and width of the histogram of the Transformed Vegetation Index TVI is controlled by the ratio of the standard deviation of the Red band to that of the NIR band. Therefore a modification of the mathematical expression of the TVI vegetation index may produce images with a varying tonality contrast. In the present paper the modified transformed vegetation index MTVI is introduced, the value of which is controlled by a positive parameter c. A theoretical study of the effect of this parameter on the image histogram is first carried out and it is shown that changing c one can obtain MTVI images with different histograms and standard deviations. Experimentation with a satellite image over western Peloponnese verifies that the parameter c controls the shape of the MTVI histogram and, furthermore, the optical effect of the MTVI image as well as the spatial variation (semivariogram) of the pixel values. Therefore the proposed modified transformed vegetation index may help the potential user in broadening his/her choices to map the vegetation cover of the area under study.